(untitled) (Revista Cerrados, 2023)
ENTREVISTADO: Vitor Sartori ENTREVISTADORES: Ana Carolina Marra de Andrade, Gabriel Andrade Perdigão, Gabriel Müller de Jesus Pinheiro Machado, Lucas de Oliveira Maciel, Júlio César Villela da Motta Filho, Rodrigo Matarelli Pereira Righi Marco Grupo de pesquisa e extensão "Tinta Vermelha".